Synthesis, Characterization, And Applications Of Coumarin Derivatives: A Short Review - Juliana Jumal; Norhanis Sakinah (USIM Press, 2024)
Coumarin and its derivatives represent one of the most active curriculums of compound possessing a broad spectrum of biological activity along with other applications such as insecticide and fragrance. There are various methodologies developed for the synthesis of coumarins. Classical routes to coumarins include Pechmann condensation, Knoevenagel condensation, Perkin reaction, and Wittig condensation reactions. Researchers have carried out adjustments and improvements to increase the efficacy and overcome the limitations from the classical route. In this review outline, coumarin derivatives were characterized by using FTIR and Hydrogen NMR spectroscopy. This review paper focuses on various synthesis and characterization techniques to analyze coumarin derivatives and their potential application in various fields.